1998
DOI: 10.1046/j.1365-2265.1998.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum granulocyte colony‐stimulating factor levels in patients with Graves' disease

Abstract: Significantly elevated serum G-CSF levels were observed in patients with Graves' hyperthyroidism. During ATD therapy, deficiency of G-CSF was not identified as a cause of agranulocytosis in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
(23 reference statements)
1
16
0
1
Order By: Relevance
“…Iitaka et al reported that serum G-CSF level in untreated patients with Graves' disease was significantly higher than that in healthy subject, but did not correlate with serum thyroid hormone levels [6]. Our study also showed that serum G-CSF levels in patients with Graves' disease did not correlate with serum FT 4 levels.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Iitaka et al reported that serum G-CSF level in untreated patients with Graves' disease was significantly higher than that in healthy subject, but did not correlate with serum thyroid hormone levels [6]. Our study also showed that serum G-CSF levels in patients with Graves' disease did not correlate with serum FT 4 levels.…”
Section: Discussionsupporting
confidence: 69%
“…Iitaka et al also reported that in 17 untreated patients with Graves' disease, the circulating neutrophil counts were relatively small (<2.0 × 10 9 /L), increased to normal after methimazole treatment, and were not related to changes in serum G-CSF level [6]. These findings suggest that in some untreated patients with Graves' disease, thyrotoxicosis may become a cause of granulocytopenia unmediated by serum G-CSF level.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Granulocyte colony-stimulating factor (G-CSF) is one of the hematopoietic cytokines, which stimulates granulocyte proliferation and activation. Serum G-CSF levels in untreated patients with Graves' hyperthyroidism were higher than those of healthy control [13], or were not different from normal subjects [14]. At least deficiency of G-CSF does not appear to be a cause of agranulocytosis by ATD.…”
Section: Discussionmentioning
confidence: 81%
“…As to the G-CSF levels in patients with Graves' disease, Iitaka et al [8] reported that they were significantly higher than those in healthy controls and positively correlated with granulocyte counts in untreated patients with Graves' disease. A positive correlation between G-CSF level and granulocyte count has also been reported in healthy individuals [7].…”
Section: Discussionmentioning
confidence: 99%